Model theory and applications : (Springer, 2011)
This title includes: Lectures - G.E. Sacks - Model theory and applications, and H.J. Keisler - Constructions in model theory; and, Seminars - M. Servi - SH formulas and generalized exponential, and J.A. Makowski - Topological model theory